The foreign direct investment job multiplier during a resource boom: Evidence from Mongolia - Nagham Sayour; Marcel Schröder (Asian Development Bank (ADB), 2021)
This paper explores the job creation impacts of the large foreign direct investment (FDI) inflows to Mongolia's non-resource sector following the signing of the investment agreement for the Oyu Tolgoi mine in 2009. Using FDI project and national employment data over 2009-2013, we employ a triple difference methodology on the sector-province (aimag)-year level. The results suggest that each FDI job and every 1 million FDI inflow displace 5.5 and 20 local jobs, respectively. Several factors may explain this result: the majority of FDI was targeted at sectors such as transportation and retail where efficiency gains led to job losses; the low skill-intensity of FDI jobs in those sectors; the low labor supply elasticity in Ulaanbaatar where most of the FDI projects are concentrated; and the limited extent of localized supply chains.
Keywords: F21; J21; O11; Q32; Q33; 330; resource boom; foreign direct investment; local job multiplier; Mongolia